2019
DOI: 10.1108/whatt-10-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Was an untapped “skilling” opportunity ignored?

Abstract: Purpose The purpose of this paper is to explore the potential of corporate social responsibility (CSR) initiatives in an Indian context, especially in the light of the “skilling India” mission initiated by the government. The aim here is to understand the dynamics of CSR initiatives and how they can be a catalyst for the training of skilled labour in support of the Indian hospitality industry. Design/methodology/approach The research is exploratory in nature and is primarily based on qualitative data. Semi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gupta (2007) in the study found a positive and crucial relationship of social responsibility in India. According to Babu and Kinkhabwala (2019), the CSR initiatives in India add positive value in bridging the labour gap and addressing the needs and demands for a skilled workforce in the country.…”
Section: Perception Study Of Job Seekers In Indiamentioning
confidence: 99%
“…Gupta (2007) in the study found a positive and crucial relationship of social responsibility in India. According to Babu and Kinkhabwala (2019), the CSR initiatives in India add positive value in bridging the labour gap and addressing the needs and demands for a skilled workforce in the country.…”
Section: Perception Study Of Job Seekers In Indiamentioning
confidence: 99%